The effects of gelatine solutions as edible coating materials on quality and sensory properties of chicken meat patties - Kilincceker, Osman; Yilmaz, Mustafa Tahsin (UNIV NAMIK KEMAL, 2016)
In this study, the effects of gelatine solutions prepared with different concentrations (0%, 5%, 7.5% and 10%) on chicken meat patties were determined. Some physical, chemical, and sensorial analyses of coated samples after frying were performed. Also, pH, TBA, and color characteristics of raw patties during storage at +4 degrees C for 15 days were evaluated. As a result, gelatine solution at level of 7.5 % increased the adhesion degree. It increased a value and enhanced sensory properties of fried samples. Gelatine solutions at level of 5 % and 7.5 % decreased TBA values of raw samples, revealing that there was no any negative effect to decrease product quality. Consequently, the coating with gelatine solution level at 7.5 % was determined to result in better quality and sensory properties than coating with those at 5 % and 10 %.
Keywords: gelatine; edible coating; chicken meat patty; Agriculture